Implementation of UI/UX Using Design Thinking Method in Tomsufood Application - Sunarya, Edwin Yohanes; Huda, Baenil; Hananto, Agustia; Hilabi, Shofa Shofiah (Fakultas Teknologi dan Ilmu Komputer Universitas Prima Indonesia, 2024)
Tomsufood is one of the online food ordering applications. To provide the best experience in ordering food, Tomsufood designed a new application product. An approach called Design Thinking was used in this study. The Design Thinking method is a software product design approach that is based on innovation and relies on problem-solving techniques. After identifying and understanding the problem obtained through the process of identifying the problem, describing the solution, empathizing with the user, and prototyping and testing. So that the Tomsufood application is able to solve problems that occur in society. The results of the study showed that the application of the Design Thinking method was able to produce a UI/UX design that was more intuitive and responsive to user needs. Users reported increased satisfaction in using the application, which included ease of navigation, clarity of information, and efficiency in the food ordering process. Keywords: UI/UX, Design Thinking, Tomsufood, User Experience